A Data-driven Approach to Astrophysics: Towards Quantum Geophysics and Quantum Astrophysics (Bulletin of Pure and Applied Sciences – Physics, 2021)
Following our previous article which recommends physicists to build models in the light of  principle of parsimony, and also a review on A. Yefremov’s research in the past few years  (PSTJ, 2021), here we discuss a data-driven approach to astrophysics. Part of inspiration for  this article came from a paper by Brunton, Proctor & Kutz (PNAS, April 12, 2016) and also  lecture by the late Hannes Alfven. We begin with a review on how Newton’s recipe to  interpret Kepler’s elliptical orbit law, actually led to a number of problematic questions.  While we agree with Alfven that one should not infer the history of solar system just from the  nature of planetary orbits (or deviations from that), and not from other present astronomy  data, because those present data may be of little value to reveal the past history; instead from  the data and improving Titius-Bode law, therefore we suggest to come up with a new  hypothesis: “quantum matter inside a Newtonian universe.” In other words, in the second  section we will discuss how quantum geophysics and quantum astrophysics emerge into the  scene.